Bioinformatics-Based Identification of Selective Cationic Amphipatic Antibacterial Peptides: Aurein 1.2 Variants Case - Polanco, Carlos; Huberman, Alberto; Uversky, Vladimir N.; Andrés, Leire; Buhse, Thomas; Castañón-González, Jorge A.; Díaz-González, Juan Luciano (Current Proteomics, 2021)
Background: Selective Cationic Amphipathic Antibacterial Peptides (SCAAPs) occupy a prominent place in the production of new drugs on account of their high toxicity towards bacteria and low toxicity towards mammalian cells, low hemolytic activity, and contribution to the protection of the human immune system. Aim: their number in nature is very low, and experimental tests are very protracted and costly. Therefore, it would be useful to have bioinformatics tools that would identify them in the existing databases and also propose new synthetic SCAAPs. Methods: In order to reduce the costs of identification and/or chemical synthesis and to know the physicochemical characteristics of SCAAPs at a residues level and to obtain a “bioiformatics fingerprint” suitable for their selection, we have modified the Polarity Index Method® (PIM®) and the α-helical configuration of each sequence is included in determining their individual “PIM® profile”. We have also used a set of the computer program to determine their “Intrinsic Disorder Predisposition”. This information was then compared with other protein groups, such as bacteria, fungi, virus and Cell-Penetrating Peptides (CPP) from the UniProt database and a set of intrinsically disordered proteins. Once the “fingerprint” of SCAAPs was obtained, it was used for searching among the 559228 “reviewed” proteins from the UniProt database and a set of synthetic SCAAPs characterized by the predefined “PIM® profile” selected. Results: Our results showed that the metric named “PIM® profile” can identify, with a high level of accuracy, a group of bacterial SCAAPs. This bioinformatics study was supported at residues level, using the in-house bioinformatics system Polarity Index Method, the commonly used algorithm for predicting intrinsic disorder predisposition, PONDR® FIT. Conclusions: The Polarity Index Method seems highly efficient in identifying SCAAP candidates.
Keywords: antimicrobial peptides